Resumo de artigo de opinião na perspectiva dos estudos linguísticos da microestrutura e da macroestrutura textual - Moraes, Otávio Brasil de (2017)
In this dissertation, our general objective is to propose the usage of the notions of microstructures and macrostructures in the production of summaries of opinion articles. Throughout the research, developed together with students of a secondary school in the city of Manaus, we have highlighted significant differences between summaries produced in the “traditional” manner and those produced according to our proposal. Our theoretical framework is Textual Linguistics of text grammars, especially the proposal by Van Dijk (1996). We have also considered the concept of text developed in the 1970’s and 80’s by Van Dijk and Kinstch. Moreover, we have highlighted more recent studies, such as Marquesi (2004), Delphino (1991) and Machado (2004). Methodologically, the research was developed as follows: initially, in the first class, we requested that students produced an abstract of an opinion article following the traditional perspective in teaching how to produce summaries, in which it is generally emphasized only the selection of the main ideas in a text. In the second class, we discussed the concepts of microstructures and macrostructures for the production of summaries, and, in the third class, we requested that students produced a second summary using those notions. We then analyzed twenty-eight summaries produced by 14 students, which allowed us to verify positive contributions from the proposal of working with textual macrostructures. The data analysis chapter contains as examples 6 summaries chosen among the 28 that were analyzed, of which 3 (three) were written with the traditional perspective and the other 3 (three) were written in the framework of microstructures and macrostructures. After, we discuss the results, which clearly point out the contributions of the studies of textual microstructures and macrostructures to the production of summaries